Atmospheric effects in geodetic levelling - Breznikar, Aleš; Aksamitauskas, Česlovas (Geodesy and Cartography, 2012)
The knowledge of physical processes and changes in the atmosphere is essential when addressing the fundamental problem, i.e. the accuracy of geodetic measurements. In levelling operations, all these changes are explained as the effect of refraction, which systematically distorts the results of levelling. Different ways of addressing the effect of refraction are represented based on the modelling of the vertical temperature gradient as the quantity that has the most influence on the refraction phenomenon.